Major incident triage: development and validation of a modified primary triage tool - Vassallo, James M A (Division of Emergency Medicine, 2019)
Introduction A key principle in the effective management of a major incident is triage, prioritising patients on the basis of their clinical acuity. However, existing methods of primary major incident triage demonstrate poor performance at identifying the Priority One patient in need of a life-saving intervention. The aim of this thesis was to derive an improved triage tool. Methods The first part of the thesis defined what constitutes a life-saving intervention. Then using a retrospective military cohort, the optimum physiological thresholds for identifying the need for life-saving intervention were determined; the combination of which was used to define the Modified Physiological Triage Tool (MPTT). The MPTT was validated using a large civilian trauma database and a prospective military cohort. Subsequently, to describe the safety profile of the MPTT, an analysis of the implications of under-triage was undertaken. Finally, pragmatic changes were made to the MPTT (MPTT-24) - in order to provide a more useable method of primary triage. Statistical analysis was conducted using sensitivities and specificities, with triage tool performance compared using a McNemar test. Results 32 interventions were considered life-saving and the optimum physiological thresholds to identify these were a GCS <14, 12 < RR <22 and a HR < 100. Within both the military and civilian populations, the MPTT outperformed all existing methods of triage with the greatest sensitivity and lowest rates of under-triage, but at the expense of over-triage. Applying pragmatic changes, the MPTT-24 had comparable performance to the MPTT and continued to outperform existing methods. Conclusion The priority of primary major incident triage is to identify patients in need of life-saving intervention and to minimise under-triage. Fulfilling these priorities, the MPTT-24 outperforms existing methods of triage and its use is recommended as an alternative to existing methods of primary major incident triage. The MPTT-24 also offers a theoretical reduction in time required to triage and uses a simplified conscious level assessment, thus allowing it to be used by less experienced providers.